Factorial validation of the university students' attitudes toward blended learning scale: An exploratory and confirmatory analysis - Taha O. Alkursheh (Journal of Pedagogical Research, 2023)
The importance of understanding student attitudes has become paramount in the successful deployment of blended learning. This study aimed to examine the factorial structure of a scale designed to assess university students' attitudes towards blended learning. Using a descriptive quantitative research approach, the study included a sample of 889 male and female students from the University of Tabuk, located in the Kingdom of Saudi Arabia. The participants were selected randomly from different academic majors and levels of study. The instrument employed in this study was the Blended Learning Attitudes Scale, a tool designed by the researcher and subjected to rigorous validation procedures. The researcher utilised exploratory and confirmatory factor analyses to understand the latent variables the scale represented comprehensively. The study's findings indicated the presence of a three-factor model, encompassing participants' perceptions of the nature of blended learning, its perceived importance, and their willingness to utilise it. The combined influence of these three factors accounted for 64% of the observed variance. The scale had noteworthy psychometric features, as evidenced by its high-reliability coefficients and robust validity indicators. This study presents a reliable instrument that educators and researchers may utilise to assess university students' attitudes towards blended learning.